1994
DOI: 10.1016/s0741-5214(94)70121-0
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal artery aneurysms: Current management and outcome

Abstract: Thrombosis of popliteal artery aneurysms can produce limb-threatening ischemia. In this setting we have found preoperative thrombolytic therapy to be beneficial. Methods: Thirty-three patients with 54 popliteal artery aneurysms were studied (mean follow-up 62 months). Twenty-one patients (62%) had bilateral popliteal artery aneurysms, and 20 patients (61%) had extrapopliteal arterial aneurysms. Thirty-three (61 %) aneurysms had symptoms of compression or ischemia, and 21 (39%) aneurysms had thrombosis. A trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 15 publications
1
92
0
7
Order By: Relevance
“…A complicação mais comum associada aos aneurismas de artéria poplítea é o risco de trombose arterial aguda acompanhado de isquemia grave, com possibilidade de amputação do membro inferior acometido [10][11][12] . Microembolizações de repetição também podem causar progressivamente um quadro de isquemia crônica importante.…”
Section: Discussionunclassified
“…A complicação mais comum associada aos aneurismas de artéria poplítea é o risco de trombose arterial aguda acompanhado de isquemia grave, com possibilidade de amputação do membro inferior acometido [10][11][12] . Microembolizações de repetição também podem causar progressivamente um quadro de isquemia crônica importante.…”
Section: Discussionunclassified
“…The risk of amputation varies between 24% and 69 % [2][3][4][5][6][7]. Moreover, untreated PAAs carry some risks of rupture or nerve compression, with potential limb dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, management of PAAs must be carefully carried out. Some authors [2,5,6,11,15,16,22] have shown that patency rates are better in elective cases, preventing distal embolization and a poor run-off [2,11,23,24]. Others risk factors justifying surgical approach are a diameter of more than 20 mm, a mural thrombus or a poor run-off, because they are predictive factors of acute thrombosis if not treated [12,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the five-year graft patency and limb salvage rates, patients with the presence of 2 or 3 runoff vessels had good results compared with single or no runoff vessel. 10) Thrombolytic therapy is useful to clear a thrombosed popliteal aneurysm and to open occluded infrapopliteal arteries. But thrombolysis can cause severe complications including major local bleeding or intracranial bleeding.…”
Section: Disseminated Intravascular Coagulation With Acutelythrombosementioning
confidence: 99%